2008
DOI: 10.1016/s0968-8080(08)32415-x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer: the sub-Saharan African perspective

Abstract: Cervical cancer is the second most common cancer in women worldwide and the leading cause of cancer deaths in developing countries. While incidence and mortality rates of cervical cancer have fallen significantly in developed countries, 83% of all new cases that occur annually and 85% of all deaths from the disease occur in developing countries. Cervical cancer is the most common cancer among women in sub-Saharan Africa. The incidence is on the increase in some countries. Knowledge and awareness of this diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
248
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(266 citation statements)
references
References 54 publications
14
248
1
3
Order By: Relevance
“…9 Human papillomavirus (HPV), the necessary cause of cervical cancer, is endemic in Africa. 10 Although there are a few published studies on HPV prevalence in sub-Saharan Africa, a recent review found HPV16 and HPV18 to be the most common HPV types in ICC, as seen in all other world regions 8 but other carcinogenic HPV types such as HPV45 and 35 are relatively more frequent compared to other world regions. 8 Data on other HPV-related anogenital cancers such as those of the vulva, vagina, anus, and penis are limited.…”
mentioning
confidence: 99%
“…9 Human papillomavirus (HPV), the necessary cause of cervical cancer, is endemic in Africa. 10 Although there are a few published studies on HPV prevalence in sub-Saharan Africa, a recent review found HPV16 and HPV18 to be the most common HPV types in ICC, as seen in all other world regions 8 but other carcinogenic HPV types such as HPV45 and 35 are relatively more frequent compared to other world regions. 8 Data on other HPV-related anogenital cancers such as those of the vulva, vagina, anus, and penis are limited.…”
mentioning
confidence: 99%
“…20,21 In conclusion therefore, it has been confirmed that the detection rate for pre-cancerous lesions of the cervix using the VIA was significantly lower than that of the Pap smear in this study which confirmed that Pap smear performed significantly better than VIA in detecting precancerous lesion of the cervix although VIA has been introduced as an alternative testing method for cervical pre-malignant lesions in low-resource countries because of the high incidence of, and mortality from, cervical cancer. 7,13,29 However, with the findings of this study, there may be need to exercise caution in the adoption of VIA as primary screening modality for cervical cancer. There may be need for more broad-based researches, training and retraining of health workers before a final decision will be taken.…”
Section: Comparison Of Via and Pap Smear Cervical Dysplasia Detectionmentioning
confidence: 81%
“…12 There is therefore a need to develop low cost screening strategies for cervical cancer which will necessarily involve the use of simple technique that can be easily taught and practiced by all medical and paramedical personnel especially in the rural areas. 13 Limitations of the study was to our inability to take cervical biopsy for definitive diagnosis was an identified limitation although our main aim was to compare the effectiveness of VIA with cervical cytology in order to adopt the suggestion of its use for mass screening. In addition, this study was hospital-based and will therefore require a complementary community-based studies in order to have a robust picture of the use of VIA among women in the community.…”
Section: Comparison Of Via and Pap Smear Cervical Dysplasia Detectionmentioning
confidence: 99%
See 2 more Smart Citations